Swedish election study 1985 - Holmberg, Sören; Gilljam, Mikael; Statistics Sweden (University of Gothenburg, 1988)
The Swedish election study 1985 was carried out in connection with the general election on September 17. Many of the questions are replications of questions asked in previous election studies. The respondent were asked about newspaper reading habits, i.e. what newspaper the respondent reads, how many days a week, which political party the newspaper supports, and interest in articles about national, local and international politics. There were also questions about the newsprograms in radio and television. The respondent had to name the most important issues in influencing vote and what issues she/he considered as the most important in the nearest future. There were also a number of questions on the opinions of the parties regarding: employment, environment, wage-earners´ investment fund, taxes, the Swedish economy, foreign affairs and security policy, social safety, and child care. Furthermore the respondent was asked to give marks from -5 to +5 to political parties, party leaders, and different formations of government during the last decade. Different issues to give own opinion on and parties´ position on: nuclear power, wage-earners´ investment fund, public sector, VAT on food, sickness benefit, and child care allowance.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

The Swedish election study 1985 was carried out in connection with the general election on September 17. Many of the questions are replications of questions asked in previous election studies. The respondent were asked about newspaper reading habits, i.e. what newspaper the respondent reads, how many days a week, which political party the newspaper supports, and interest in articles about national, local and international politics. There were also questions about the newsprograms in radio and television. The respondent had to name the most important issues in influencing vote and what issues she/he considered as the most important in the nearest future. There were also a number of questions on the opinions of the parties regarding: employment, environment, wage-earners´ investment fund, taxes, the Swedish economy, foreign affairs and security policy, social safety, and child care. Furthermore the respondent was asked to give marks from -5 to +5 to political parties, party leaders, and different formations of government during the last decade. Different issues to give own opinion on and parties´ position on: nuclear power, wage-earners´ investment fund, public sector, VAT on food, sickness benefit, and child care allowance.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 1985
VU85
Keywords: developing countries; utvecklingsland; elections; val; mass media; massmedia; occupations; yrken; participation; deltagande; politics; politik; public sector; offentlig sektor; religion; religion; social mobility; social rörlighet; ethics; etik; energy; energi; parliamentary elections; riksdagsval; political interest; politiskt intresse; political behaviour; politiskt beteende; taxation; beskattning; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; political parties; politiska partier; illegal drugs; illegal drog; electoral issues; valfrågor; trade unions; fackföreningar; organizations; organisationer; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; minority groups; minoritetsgrupp; political party policies; politiska partiers politik; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap